Performance of lentil-mungbean-T.aus rice-T.aman rice against existing cropping pattern lentil-jute-T.aman rice in Faridpur region (Bangladesh Journal of Agricultural Research, 2019)
A trial was conducted in the farmers’ field at Farming Systems Research and Development (FSRD) site, Hatgobindapur, Faridpur during 2014-15 and 2015-16 to develop an alternate cropping pattern over existing cropping pattern for increasing cropping intensity, total productivity as well as farmers’ income. The alternate cropping pattern Lentil (var. BARI Masur-7)- Mungbean (var. BARI Mung- 6)- T. Aus rice (var. BRRI dhan48)- T.Aman rice (var. BRRI dhan62) was tested against the existing cropping pattern Lentil (var. Local)- Jute (var. JRO 524)- T.Aman rice (var. BRRI dhan33). All the four crops in the AP were grown successfully within stipulated time frame following recommended practices. Crop duration and turn around time in alternate cropping pattern were 340 days and 25 days while that in existing cropping pattern were 313 days and 52 days, respectively. Cropping intensity increased from 300% (in existing pattern) to 400% in the alternate cropping pattern. Two years results showed that, average yield of T.Aus rice, T.Aman rice, Lentil and Mungbean in the alternate cropping pattern were 3.75, 4.17, 1.31 and 0.80 t ha-1, respectively. The rice equivalent yield and production efficiency was increased by 18 and 35%, respectively over existing pattern. The gross margin of the whole alternate cropping pattern was Tk.106304 ha-1whereas Tk. 75480 ha-1from existing cropping pattern. The alternate pattern provided 41% higher gross margin over existing cropping pattern. The MBCR was 4.86 over existing cropping pattern.Bangladesh J. Agril. Res. 44(3): 537-552, September 2019